The Suluk of The Salik in the Concept of Seven Stages (Martabat Tujuh) of Abdel Samad al-Palimbani - Syukri Alfauzi Harlis; Arrasyid Arrasyid (Jurnal Theologia, 2022)
This article aims to reveal how the idea of Abdel Samad al-Palimbani on Seven Stages (Martabat Tujuh) is considered controversial by some Muslims. The reason is that this idea is part of the concept of embodiment in the frame of philosophical Sufism. The seven stages essentially are to prove humans as the most perfect creation compared to others. This paper uses the library research method based on primary and secondary sources. This paper attempts to reveal al-Palimbani's ideas related to the seven stages concept. These seven stages discussed Salik's position as caliph on the earth. A Salik is always eager to find the best way to arrive at the paran. The idea of The Seven Stages is to know how close a man is to his Creator. For Salik's is to know their position as being who manifests God’s Tajalli. Unfortunately, such an idea is not fully implemented, even among Islamic thinkers themselves it has been considered heretical and forbidden. This paper showed that the seven stages are the unique condition that must be understood by all Muslims who are concerned with Islamic esoteric studies to know the autentic reality.